1996
DOI: 10.1136/bmj.313.7053.344
|View full text |Cite
|
Sign up to set email alerts
|

Use of oral corticosteroids in the community and the prevention of secondary osteoporosis: a cross sectional study

Abstract: Objective-To determine the prevalence of continuous use of oral steroids in the general population, the conditions for which they are prescribed, and the extent to which patients taking oral steroids are taking treatment to prevent osteoporosis.Design-A cross sectional study with a four year retrospective review of drug treatment.Setting-Eight large general practices in central and southern Nottinghamshire.Subjects-A population of 65 786 patients (52% women) registered with a general practitioner during 1995.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
85
1
5

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(103 citation statements)
references
References 24 publications
6
85
1
5
Order By: Relevance
“…The high frequency of ever CS users (11% in controls vs. 0.9% current users in the study by van Staa et al [3]) was due to the advanced age of the case and thus also control subjects. The use of CS increases with age [2], and the mean age of 78 years was much higher than in previous population-based studies [2,3]. Furthermore, previous studies report current use (prevalence) whereas the present study reports ever (cumulated) use.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…The high frequency of ever CS users (11% in controls vs. 0.9% current users in the study by van Staa et al [3]) was due to the advanced age of the case and thus also control subjects. The use of CS increases with age [2], and the mean age of 78 years was much higher than in previous population-based studies [2,3]. Furthermore, previous studies report current use (prevalence) whereas the present study reports ever (cumulated) use.…”
Section: Discussioncontrasting
confidence: 75%
“…Two recent cross-sectional drug-utilization studies from the UK have reported a high prevalence of CS use of 0.5% [2] and 0.9% [3], respectively. The prevalence of CS users increased with age: 1.4% of all subjects aged ‡55 years had used CS for more than 3 months [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Community survey data estimate the frequency of oral glucocorticoid use as 0.5% of the general population and 1.75% of women Ͼ55 years of age (1,2). Glucocorticoids still play a decisive role in the management of diverse rheumatic conditions due to their powerful antiinflammatory and immunosuppressive properties.…”
Section: Introductionmentioning
confidence: 99%
“…A 1997 survey of consultant ophthalmologists 1 showed that three quarters prescribed steroids in significant doses but that only 25% of these gave advice to patients on the prevention of osteoporosis. A 1999 study in general practice 2 showed that only 14% of steroid users were prescribed prophylactic treatment against bone loss. Although the literature on steroidinduced osteoporosis is now extensive, it has been largely confined to the rheumatological and specialist medical literature.…”
Section: Introductionmentioning
confidence: 99%